Use of headphones for the delivery of music programs for people with dementia in long-term care homes: a scoping review - Huang, Yaqi; Wong, Karen Lok Yi; Cheung, Daphne Sze Ki; Yeo, Myung Sun; Kim, Soo Ji; Sue, Macdonald; Hung, Lillian (Frontiers in Dementia, 2026)
ObjectiveTo examine the evidence regarding to the use of headphones in music programs for people with dementia in long-term care homes (LTC) and identify enablers and barriers to its implementation.IntroductionHeadphones can provide an immersive auditory experience, powerfully stimulating memories and evoking emotional expression. However, reviews on factors influencing their implementation in LTC settings are limited.MethodsThis review followed the Joanna Briggs Institute methodology and was reported according to the PRISMA-ScR Checklist. A search was conducted across databases, including PubMed, CINAHL, Embase, Web of Science, Scopus, PsycINFO, and ProQuest. Studies were included if they explicitly delivered the music program using headphones for people with dementia in LTC homes. Data were extracted and thematically synthesized to identify key enablers and barriers to headphone use and program implementation.ResultsA total of 21 studies were included. Music delivered via headphones demonstrated significant potential to pain relief, reduce the behavioral and psychological symptoms, delirium, control hyperactive behavior, and improve sleep quality. The key enablers for its implementation included (1) Comfortable and immersive experience, (2) Good accessibility and sustainability, (3) Enhanced engagement and interactions and (4) Appropriate staff training and collaboration. Barriers included (a) Less optimal headphone options in dementia care, (b) Staff burden and shortage, (c) Operational challenges, and (d) Music selection and personalization challenges.ConclusionThis scoping review identifies key enablers and barriers to implementing headphone-based music programs for people with dementia in LTC homes. Future research should develop strategies for optimal headphone use, staff collaboration, and personalized music delivery to support sustainable and effective implementation.